1978
DOI: 10.1002/eji.1830080910
|View full text |Cite
|
Sign up to set email alerts
|

Role of membrane receptors in the induction of an in vitro secondary anti‐hapten response I. Differentiation of B memory cells to plasma cells is independent of antigen‐immunoglobulin receptor interaction

Abstract: In these experiments, we show that the interaction of antigen and B cell surface immunoglobulin is not essential for the generation of an IgG in vitro response to the hapten p-azophenyl-lactoside (lac). In our experimental system, keyhole limpet hemocyanin (KLH) was first selectively attached either to H-2, Ia or Ig receptors of lac-primed B cells by a hapten sandwich technique or to Fc receptors by complexes of azophenyl arsonate (ars)-coupled KLH and anti-ars. The labeled cells were then cultured with KLH-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1978
1978
1984
1984

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…The assumption appears reasonable because the frequencies of LPS-induced PFC are in fact identical to the frequencies of LPS-reactive B cells of the same specificities, when determined in limiting-dilution conditions (7). These observations confirm previous reports that T cell-dependent B-cell activation could take place in the absence of specific interactions with Ig receptors of the responding cells (18), when memory cells were used, and they establish that this is also the case for normal, unprimed B cells.…”
Section: Polyclonality Of the T Cell-dependent B-cell Response The Msupporting
confidence: 91%
See 1 more Smart Citation
“…The assumption appears reasonable because the frequencies of LPS-induced PFC are in fact identical to the frequencies of LPS-reactive B cells of the same specificities, when determined in limiting-dilution conditions (7). These observations confirm previous reports that T cell-dependent B-cell activation could take place in the absence of specific interactions with Ig receptors of the responding cells (18), when memory cells were used, and they establish that this is also the case for normal, unprimed B cells.…”
Section: Polyclonality Of the T Cell-dependent B-cell Response The Msupporting
confidence: 91%
“…Some, however, dealt with T-cell recognition of Ig idiotypes on responding B cells and are, therefore, equivalent to oligoclonal, antigen-dependent cooperation (35,36). Others, although bypassing Bcell Ig receptors, did not use enriched T cells and studied only the responses of antigen-specific B cells (18).…”
Section: Discussionmentioning
confidence: 99%
“…As an assay system we chose the activation of B cells to plaque-forming cells (PFC) by I-A compatible THy in the presence of the specific antigen. This model system was first described by Cammisuli et al [9], using a hapten-antibody sandwich technique to bridge T and B cells, and has since been employed by many investigators [lo-121, In our case, the THy would bind to the B cell because they would recognize antigen presented by la molecules on the B cell surface. Surprisingly, only the A chain-reactive THy were able to induce polyclonal B cell activation in the presence of beef insulin.…”
Section: Introductionmentioning
confidence: 94%
“…One avenue of B cell triggering which is not considered in Figure !, is the activation of B cells via direct ("cognate") interactions with T cells. Several groups have observed that activated T cells are capable of triggering most, if not all, resting B lymphocytes to proliferation and Ig secretion without the requirement for the cross-linkage ofthe B cell's membrane Ig (Cammisuli et al 1978, Marrack & Kappler 1980, Augustin & Coutinho 1980, Tse et al 1981, Martinez-Alonso & Coutinho 1981, Jones & Janeway 1981. This finding has rekindled doubts about the role of Ig molecules as true receptors involved in B cell activation and has fortified earlier models proposing that membrane-bound Ig serves only to focus T cell signals (i.e., the true activation signals) onto resting B cells (Coutinho & Moller 1974).…”
Section: T Cell Triggering Of B Cellsmentioning
confidence: 99%
“…However, it does not appear that one can explain those instances of cognate help in which receptor cross-linkage does not occur simply by the local production of BMF. There is considerable evidence that substantial B cell proliferation occurs in instances in which T cells help B cell responses by recognizing B cell membrane antigens (Augustin & Continho 1980), or by recognizing exogeneous antigens bound non-specifically to B cell membranes (Cammisuli et al 1978, Marrack & Kappler 1980, Tse et al 1981, Jones & Janeway 1980). Recently, DeFranco etal.…”
Section: T Cell Triggering Of B Cellsmentioning
confidence: 99%